If the function $f:[1,\;\infty ) \to [1,\;\infty )$ is defined by $f(x) = {2^{x(x - 1)}},$ then ${f^{ - 1}} (x)$ is
${\left( {\frac{1}{2}} \right)^{x(x - 1)}}$
$\frac{1}{2}(1 + \sqrt {1 + 4{{\log }_2}x} )$
$\frac{1}{2}(1 - \sqrt {1 + 4{{\log }_2}x} )$
Not defined
Let $S=\{a, b, c\}$ and $T=\{1,2,3\} .$ Find $F^{-1}$ of the following functions $F$ from $S$ to $T$. if it exists. $F =\{( a , 2)\,,(b , 1),\,( c , 1)\}$
Let $f : R \rightarrow R\ f(x) = x^3 -3x^2 + 3x\ -2$ , then $f^{-1}(x)$ is given by
The inverse function of $f(\mathrm{x})=\frac{8^{2 \mathrm{x}}-8^{-2 \mathrm{x}}}{8^{2 \mathrm{x}}+8^{-2 \mathrm{x}}}, \mathrm{x} \in(-1,1),$ is
Consider $f: R \rightarrow R$ given by $f(x)=4 x+3 .$ Show that $f$ is invertible. Find the inverse of $f$
Let $Y =\left\{n^{2}: n \in N \right\} \subset N .$ Consider $f: N \rightarrow Y$ as $f(n)=n^{2}$ Show that $f$ is invertible. Find the inverse of $f$